Dance, body and memory: the Original Ballet Russe and its three seasons in Rio de Janeiro - Cerbino, Beatriz (Revista Brasileira de Estudos da Presença, 2021)
This text presents reflections on studies of history, memory and dance. I start from the field of History and my interest in understanding the role of memory in knowledge production processes. As a case study, I examine the three Original Ballet Russe seasons in the city of Rio de Janeiro, which took place in 1942, 1944 and 1946. During this period, the company was seen as exemplary in its contribution to the building of Brazilian national ballet. I demonstrate how the discourse employed by the local press fueled these ideas. Guided by the methodological procedures of cultural history, I use dance critic Jaques Corseuil’s reviews as key sources.